Analisis CSR, GCG dan Keputusan Investasi pada Perusahaan Konstruksi yang Terdaftar di Bursa Efek Indonesia - Devayanty, Raras; Muazaroh, Muazaroh (Ekonomis: Journal of Economics and Business, 2024)
Profitability of a company is the company's ability to obtain net profit from activities carried out during the accounting period. The purpose of this research is to examine and describe the effect of corporate social responsibility, good corporate governance, and investment decisions on profitability. The number of samples is 48 construction company data with purposive sampling criteria. The analysis technique used is the F-test, and multiple linear regression with the t hypothesis test. The results of the study show that corporate social responsibility has a significant negative effect on profitability, while good corporate governance and investment decisions have an insignificant negative effect on profitability.